VIEWS OF USUL FIQIH AND ISLAMIC FAMILY LAW ON CONCERNED MARRIAGE CASES IN PADANG CITY - Firdaus Hisab; Mursal Mursal; Desminar Desminar; Syaflin Halim (Universitas Islam Negeri Ar-Raniry, 2023)
This research aims to explore the perspectives on consanguineous marriage in the context of Islamic jurisprudence (usul fiqh) and Islamic family law. Research adopts a comparative and descriptive approach, gathering primary data through in-depth interviews with experts in Islamic jurisprudence and Islamic family law. The findings reveal that consanguineous marriage is firmly grounded in Islamic law, with its theological basis found in the Quran and Hadith, which unequivocally prohibit it. However, variations exist in the interpretation and emphasis between usul fiqh and Islamic family law perspectives. Social and cultural factors influence the occurrence of consanguineous marriages, with differing community understandings in Kota Padang being a key factor in disparate viewpoints. Despite these distinctions, there are commonalities, such as the prohibition of consanguineous marriage, the reliance on the Quran and Hadith as legal foundations, and the acknowledgment of negative consequences by both perspectives. Lastly, the legal principles underpinning these views in both fields center on concepts such as maslahah (public interest), maqasid syariah (objectives of Islamic law), and ta'addud al-asbab (consideration of circumstances), all aimed at safeguarding the welfare of humanity. While emphasis may differ, these principles serve as guiding frameworks for understanding the phenomenon of consanguineous marriage in Kota Padang